Clinical outcomes of transcatheter aortic valve replacement in patients with radiation-induced aortic stenosis: a systematic review and meta-analysis - Daniyal Ameen; Nisarg Thakker; Rafael Contreras; Seyyed Mohammad Hashemi; Amir Nasrollahizadeh; Parsa Saberian; Dona Kuriyakose; Ehsan Amini-Salehi; Narsimha Rao Keetha; Sandeep Samethadka Nayak (Frontiers in Cardiovascular Medicine)
BackgroundTranscatheter aortic valve replacement (TAVR) is an effective treatment for severe aortic stenosis, particularly in high-risk patients unsuitable for surgical aortic valve replacement (SAVR). However, the efficacy of TAVR in patients with radiation-induced aortic stenosis remains uncertain and controversial. This meta-analysis evaluates clinical outcomes of TAVR in patients with prior chest radiation (C-XRT).MethodsA comprehensive literature search of PubMed, Scopus, and Web of Science databases was conducted through September 15, 2024. Studies comparing TAVR outcomes in patients with and without prior chest radiation were included. Statistical analysis used STATA software with a random-effects model, incorporating Knapp-Hartung correction and prediction intervals. Publication bias was assessed using funnel plots, Egger's test, Begg's test, and the trim-and-fill method.ResultsThe meta-analysis found no significant differences in short-term outcomes between patients with and without C-XRT. In-hospital mortality (OR: 0.81; 95% CI: 0.14–4.69), 30-day mortality (OR: 1.59; 95% CI: 0.71–3.55), and 1-year mortality (OR: 1.15; 95% CI: 0.52–2.54) were comparable. Similarly, rates of in-hospital myocardial infarction, stroke, and major bleeding showed no significant differences. The GRADE assessment indicated very low-quality evidence for most outcomes, including in-hospital mortality and stroke, and low-quality evidence for outcomes like 30-day stroke and acute kidney injury.ConclusionTAVR appears effective in patients with prior chest radiation, with comparable short-term outcomes to non-C-XRT patients. However, due to significant heterogeneity across the included studies and the low to very low quality of evidence, these findings should be interpreted with caution. The current data remains inconclusive, and further high-quality, prospective studies with longer follow-up periods are essential to better understand the long-term risks and confirm the safety and efficacy of TAVR in this patient population.Systematic Review RegistrationPROSPERO CRD42024593497.